Analisis Hubungan antara Nilai, Kepuasan dan Loyalitas Nasabah Perbankan di Sulawesi Selatan - Mattalatta - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objective of this research are: 1) To develop and to implementate of methode to identificate of relationship between value, satisfaction and customer loyalty. 2)To know of effect satisfaction level toward customer loyalty. 3) To find out of relation between value perception, adequate satisfaction, desired satisfaction level and saving customer loyalty. 4) To find of factors influence of attitude and behavior loyalty of bank. 5) To identificate loyalty level according customer characteristic. The result of the analysis shows that a)relation between value perception toward attribute performance its significant and positive. b) adequate and desired satisfaction level of saving customer in South Sulawesi, the greatest influence by professionalism staff. c) the relation between adequate satisfaction and customer loyalty its significant and negative.d) found directly relation between value variable and loyalty variable in South Sulawesi. e) customer bank in generally which South Sulawesi have spurious loyalty. The population of this research is the general customer of bank, either goverment or non government customer are in South Sulawesi. The sampels take from., a) totaling sampels is minimal 912 persons. For this research the sampels took about 1346 customers, b) toward sampel area took by cluster sampling, according to four area where the customer live.Keywords: value perception, adequate and desired satisfaction,and loyalty.